2008
DOI: 10.1002/ijc.23653
|View full text |Cite
|
Sign up to set email alerts
|

Catecholestrogens induce oxidative stress and malignant transformation in human endometrial glandular cells: Protective effect of catechol‐O‐methyltransferase

Abstract: Prolonged exposure to unopposed estrogens is a major risk factor for the development of endometrial cancer. Oxidative metabolism of estradiol (E 2 ) into the catecholestrogens (CEs), 4-hydroxyestradiol (4-OHE 2 ) and 2-hydroxyestradiol (2-OHE 2 ), may play an important role in estrogen carcinogenicity. CEs can be oxidized to the corresponding ortho-quinone derivatives with concomitant formation of the reactive oxygen species (ROS). Catechol-O-methyltransferase (COMT) is the major enzyme involved in the detoxif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 57 publications
3
36
0
1
Order By: Relevance
“…HuLM cells were seeded into 96-well plates. Cells were treated with medium containing 0, 0.1, 0.5, 1, 5, and 10 M simvastatin, and the MTT assay was performed as described previously (30). We chose to investigate doses of simvastatin ranging from 0.1-10 M. This decision was made on the basis of dosages currently used to treat hypercholesterolemia (up to 1 mg/kg body weight/day), which is associated with peak serum levels of ϳ0.3 M (31, 32).…”
Section: Methodsmentioning
confidence: 99%
“…HuLM cells were seeded into 96-well plates. Cells were treated with medium containing 0, 0.1, 0.5, 1, 5, and 10 M simvastatin, and the MTT assay was performed as described previously (30). We chose to investigate doses of simvastatin ranging from 0.1-10 M. This decision was made on the basis of dosages currently used to treat hypercholesterolemia (up to 1 mg/kg body weight/day), which is associated with peak serum levels of ϳ0.3 M (31, 32).…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular ROS accumulation in response to treatment with IR with or without cotreatment with 2ME was determined using the fluorescent probe 2,7'-dichlorodihydrofluoresceindiacetate (DCFH-DA) for 30 min, as previously described (19).…”
Section: Measurement Of Intracellular Ros Accumulationmentioning
confidence: 99%
“…Cell cycle analysis was determined in MCF-7/FIR cells treated with 2ME and/or IR as previously described (19).…”
Section: Cell Cycle Analysis By Flow Cytometrymentioning
confidence: 99%
“…Animal experiments showed a mutagenic effect of 4-hydroxyestradiolquinones (33,34). Of further interest are the results of Salama et al (35), who demonstrated that catechol oestrogens induce oxidative stress in human endometrial cells and trigger malignant transformation that was inhibited by addition of catechol-O-methyltransferase.…”
Section: -Hydroxyoestrogensmentioning
confidence: 96%